2017
DOI: 10.1051/epjconf/201714006015
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of multi-sphere and superquadric particle representation for modelling shearing and flow characteristics of granular assemblies

Abstract: In the current study, complex-shaped particles are simulated with the Discrete Element Method (DEM) using two different approaches, namely Multi-spheres (MS) and Superquadrics (SQ). Both methods have been used by researchers to represent the shape of real particles. However, despite the growing popularity of utilizing MS and SQ particles in DEM simulations, few insights have been given on the comparison of the macro scale characteristics arising from the two methods. In this respect, initially the characterist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…In a previous study [28,29], we have compared the influence of multi-sphere bumpiness and superquadric blockiness on the response of assemblies of cubical particles in several micro-and macro-scale tests. We have observed that singleparticle behaviour is a direct function of both surface and edge properties, and that shape complexity only significantly affects the shear strength, porosity and mode of motion once the packing is dense.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study [28,29], we have compared the influence of multi-sphere bumpiness and superquadric blockiness on the response of assemblies of cubical particles in several micro-and macro-scale tests. We have observed that singleparticle behaviour is a direct function of both surface and edge properties, and that shape complexity only significantly affects the shear strength, porosity and mode of motion once the packing is dense.…”
Section: Introductionmentioning
confidence: 99%
“…In this description, spheres are allowed to overlap and be glued together to approximate an arbitrarily shaped particle. On the other hand, irregular particle shapes can alternatively be idealized to some regular shapes such as spheroids, cuboids or cylinders that can be approximated by superquadric (SQ) shapes [9,10,11]. It has been suggested that 80% of all shapes can be represented by superquadric functions or derived from superquadrics in higher-dimensional hyperquadrics [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…On one hand, this might be counterintuitive, as elongated grains undergo shear induced orientational ordering with their average orientation pointing almost in the direction of the flow lines [7][8][9][10][11]. On the other hand, several authors have shown, that for other nonspherical grains increasing grain angularity (or in other words increasing effective friction of the material) reduces the mass flow rate [3,4,[12][13][14][15], and leads to larger stagnant zones and more residual mass after discharge [12,13,16,17]. Several authors detected and quantified fluctuations in the discharge rate or flow field [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%